Family Resemblances in Action: An Introduction to Religiopolitical Activism in Southern Africa - Dijk, Rijk van (KOPS Universität Konstanz, 2021)
The introduction to this special issue argues that in many countries in southern Africa a new phase in the entanglement between the religious and the political has set in. Increasingly, activists in political fields are borrowing from religious registers of discourse and practice, while conversely, activists in the religious domain are adopting discourses and practices originating in the political domain. We suggest that this religiopolitical activism is simultaneously the product of a climate of profound social change and an important transformative force within it. In order to do justice to the complex dynamics of southern African religiopolitical activism in its manifold manifestations, we draw on the concept of ‘family resemblances’. This allows us to examine how the boundaries between religious and political registers are made the object of situated social negotiations. The family resemblances explored in this special issue range from religiopolitical activists’ habitus and their communication strategies via religious leaders’ self-positionings in relation to the political, to the creation of specific religiopolitical spaces.